2011
DOI: 10.1111/j.1398-9995.2011.02758.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of pre‐coseasonal and continuous grass sublingual immunotherapy in children

Abstract: Both protocols were effective compared with placebo and showed similar decreases for combined symptoms/medication score and all secondary endpoints, with the exception of nasal symptoms that were lower in the pre-coseasonal group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
0
50
0
3
Order By: Relevance
“…91,92 Some heterogeneity between adult studies, low risk of severe systemic allergic side-effects. | 773…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…91,92 Some heterogeneity between adult studies, low risk of severe systemic allergic side-effects. | 773…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…The different JC pollen counts in the 2 seasons make it difficult to compare treatment scores with certainty, and many of the patients in this study were not treated for 4 months prior to pollen dispersal in the 1st season. Recent studies have compared pre-coseasonal, coseasonal and continuous administration of SLIT [10,21]; however, it is difficult to conclude that continuous treatment over multiple seasons provides better efficacy. Most side effects in our study were mild and were related to the site of administration (mouth oedema, stomatitis and throat irritation).…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies reported local reactions in 0.2% to 50% of patients receiving SLIT and 6% to 25% of patients receiving placebo. 22,25,[27][28][29][30][31][35][36][37] Systemic reactions were commonly reported in both the SLIT and placebo groups, but no life-threatening reactions, anaphylaxis, or deaths were reported in these trials. to least commonly reported, the symptoms or reactions were characterized as general, gastrointestinal, ocular, respiratory, and cutaneous.…”
Section: Safety Of Slit In Childrenmentioning
confidence: 99%